Decarboxylative couplings as versatile tools for late‐stage peptide modifications. Issue 3 (3rd March 2018) - Malins, Lara R.
Abstract: While strategies for the late‐stage modification of peptides are crucial to the design and synthesis of new peptide‐based materials and therapeutics, synthetic methods have historically focused on the modification of select, nucleophilic amino acids. This review highlights decarboxylative coupling strategies as emerging tools for the targeted functionalization of native peptidic acids—α‐carboxylic acids and aspartic/glutamic acid residues—through complexity building CC and Cheteroatom bond formations. Decarboxylation strategies employing both activated carboxylic acids (redox‐active esters) and the direct application of unprotected carboxylic acids are discussed. Emphasis is placed on the scope and limitations of the methodologies as well as their compatibility with complex peptide substrates. Abstract :